2023
DOI: 10.1101/2023.09.26.559591
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating goodness-of-fit of animal movement models using lineups

John Fieberg,
Smith Freeman,
Johannes Signer

Abstract: Models of animal movement are frequently fit to animal location data to understand how animals respond to and interact with local environmental features. Several open-source software packages are available for analyzing animal movements and can facilitate parameter estimation, yet there are relatively few methods available for evaluating model goodness-of-fit. We describe how a simple graphical technique, thelineup protocol, can be used to evaluate goodness-of-fit of integrated step-selection analyses and hidd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…First, simulated and observed paths can be visually compared (Figure 3). If the model has been specified in a way that describes the data-generating process reasonably well, the observed path should not stand out when compared to simulated paths (Fieberg et al, 2023). Similar to our case study, one can evaluate whether the observed and simulated paths exhibit similar behaviour near roads, rivers, or other prominent environmental features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, simulated and observed paths can be visually compared (Figure 3). If the model has been specified in a way that describes the data-generating process reasonably well, the observed path should not stand out when compared to simulated paths (Fieberg et al, 2023). Similar to our case study, one can evaluate whether the observed and simulated paths exhibit similar behaviour near roads, rivers, or other prominent environmental features.…”
Section: Discussionmentioning
confidence: 99%
“…elevation could also be important), but we conclude that Model 3 is already a significant improvement over Model 1. Many realisations of this simulation could be used to formally measure the predictive power of each model (Potts et al, 2022) and to formally evaluate model goodness-of-fit (Fieberg et al, 2023).…”
Section: African Buffalomentioning
confidence: 99%
See 1 more Smart Citation
“…Assessing the accuracy of simulations to different covariates is therefore important, and we suggest following a summary statistic approach as we have taken here, giving more weight to summary statistics that represent movement characteristics relating to the research question. An approach to assess the more qualitative aspects of the overall trajectory would be the 'lineup' approach (Fieberg et al, 2023), as many of the trajectories appeared visually similar to the observed data. We also advocate for using simulations as a means of model selection and to investigate drivers of animal movement decisions (Potts, Börger, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We have archived the data and code needed to reproduce all analyses in the paper in the Data Repository of the University of Minnesota (Fieberg et al., 2024), https://doi.org/10.13020/3m0d-mp29.…”
Section: Peer Reviewmentioning
confidence: 99%